2018
DOI: 10.1016/j.mhpa.2018.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Does level of leisure time physical activity, in a sample of patients with depression, predict health care utilization over a subsequent 5-year period? Findings from a Finnish cohort study

Abstract: Objectives:The main aim of this study was to investigate the association between leisure time physical activity (LTPA) and health care utilization (HCU) and furthermore, socio-demographic and clinical factors according to LTPA level among depressed patients based on data drawn from the Finnish Depression and Metabolic Syndrome in Adults (FDMSA) -study (2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016). Methods: 447 depressed patients aged 35-65 from municipalities within the Central Finland Hospital District par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…Blood pressure was measured twice after 15 min rest time with a mercury sphygmomanometer and the patient in a sitting position. The physical examination was conducted by trained study nurses [22]. The body mass index (BMI) was defined as the person's weight (kg) divided by the square of the height (m).…”
Section: Methodsmentioning
confidence: 99%
“…Blood pressure was measured twice after 15 min rest time with a mercury sphygmomanometer and the patient in a sitting position. The physical examination was conducted by trained study nurses [22]. The body mass index (BMI) was defined as the person's weight (kg) divided by the square of the height (m).…”
Section: Methodsmentioning
confidence: 99%
“…Leisure-time physical activity (number of 30-min exercise sessions) was delineated with the question: "How often do you engage in physical activity for at least half an hour so that you are out of breath and sweating?" Replies were classified as low (0-2 sessions per month), moderate (1-2 sessions per week), or high (three or more sessions per week) (16,25).…”
Section: Methodsmentioning
confidence: 99%
“…The study protocol was approved by the Ethics Committee of the Central Finland Hospital District. The FDMSA -study has been reported in previous studies [31][32][33][34][35].…”
Section: Methodsmentioning
confidence: 99%
“…Leisure-time physical activity was determined with the question:" How often do you do physical activity at least half on hour so that you are out of breath and sweating?" then answers were classified as low (0-2 sessions per month), moderate (1-2 sessions per week), or high (three or more sessions per week) [35].…”
Section: Methodsmentioning
confidence: 99%